Corporate Social Responsibility, Brand Loyalty di Universitas Negeri dan Swasta di Kota Batam - Saputra, Suyono; Charles, Hendry (E-Jurnal Akuntansi; Vol 33 No 11 (2023)DO - 10.24843/EJA.2023.v33.i11.p03, 2023)
The aim of the research is to identify factors in implementing Corporate Social Responsibility (CSR) that influence Brand loyalty both directly and indirectly through the mediation of Brand Trust, Brand Reputation and Brand Image. The research population is active students at state universities and private universities in Batam City. The data collection technique used was primary data by distributing questionnaires to 420 students in Batam City. The data analysis technique uses PLS-SEM which aims to test latent constructs in the linear construct relationship with existing parameters. Based on research results, CSR has a significant positive effect on brand loyalty, brand image, brand trust and brand reputation in the state and private universities in Batam City. Meanwhile, brand trust and brand loyalty do not have a significant influence due to the lack of trust and interest of students in state and private universities. Keywords: CSR; Brand Loyalty; Brand Trust; Brand Reputation; Brand Image.